2009
DOI: 10.1111/j.1528-1167.2009.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

A new rapid micromethod for the assay of phenobarbital from dried blood spots by LC‐tandem mass spectrometry

Abstract: SUMMARYAdvantages of dried blood spot include low invasiveness, ease and low cost of sample collection, transport, and storage. We used tandem mass spectrometry (LC-MS/MS) to determine phenobarbital levels on dried blood spot specimens and compared this methodology to commercially available particle enhanced turbidimetric inhibition immunoassay (PETINIA) in plasma/serum samples. The calibration curve in matrix using D 5 -phenobarbital as internal standard was linear in the phenobarbital concentration range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 12 publications
0
29
0
1
Order By: Relevance
“…The acceptable LLOQ is defi ned as the lowest analyte concentration that gives accuracy within ±20% (bias) of the nominal value and precision ≤20% (CV) from six replicates for a predefi ned dynamic range. Considering the limited blood volume taken from a punch, a larger punch or multiple punches make the lower concentration of analyte measurable (Alfazil and Anderson, 2008;Garcia Boy et al, 2008;Burhenne et al, 2008;Gempel et al, 2000;Higashi et al, 2008;la Marca et al, 2008bla Marca et al, , 2009Liang et al, 2009). On the other hand, a larger punch from a small spot might result in a better reproducibility and a small punch from a large area might be one of the sources of poor assay precision due to the chromatographic eff ect (Hoogtanders et al, 2007).…”
Section: Assay Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The acceptable LLOQ is defi ned as the lowest analyte concentration that gives accuracy within ±20% (bias) of the nominal value and precision ≤20% (CV) from six replicates for a predefi ned dynamic range. Considering the limited blood volume taken from a punch, a larger punch or multiple punches make the lower concentration of analyte measurable (Alfazil and Anderson, 2008;Garcia Boy et al, 2008;Burhenne et al, 2008;Gempel et al, 2000;Higashi et al, 2008;la Marca et al, 2008bla Marca et al, , 2009Liang et al, 2009). On the other hand, a larger punch from a small spot might result in a better reproducibility and a small punch from a large area might be one of the sources of poor assay precision due to the chromatographic eff ect (Hoogtanders et al, 2007).…”
Section: Assay Performancementioning
confidence: 99%
“…Second, it off ers a simpler storage and easier transfer because there is no requirement for freezers or dry ice in most applications. DBS can be conveniently collected by patients themselves or guardians with minimum training and sent by mail to the assigned laboratory, avoiding unnecessary costs (Garcia Boy et al, 2008;la Marca et al, 2009). Third, DBS reduces the infection risk of HIV/AIDS and other infectious pathogens to a minimum (Parker and Cubit, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies recently evaluated the use of DBS for therapeutic drug monitoring (TDM) and toxicology in adults [9,10]. Some studies, also from our group, applied the DBS technique to evaluate drug concentrations in newborns, infants and children [11][12][13][14][15]. These reports showed that the accuracy of TDM studies using DBS is comparable to that of traditional TDM studies on plasma which require larger blood volumes.…”
Section: Introductionmentioning
confidence: 66%
“…An attracting and potential method to easily obtain samples for PK studies and TDM in children is collection of whole blood samples onto filter paper (dried blood spot or DBS) [7][8][9][10][11][12]. DBS are commonly used for neonatal screening of metabolic diseases, cystic fibrosis and hypothyroidism in micro-blood samples.…”
Section: Introductionmentioning
confidence: 99%
“…DBS are commonly used for neonatal screening of metabolic diseases, cystic fibrosis and hypothyroidism in micro-blood samples. Some studies recently evaluated the use of DBS for TDM and toxicology in adults [7][8][9][10][11][12]. Some authors, also from our group, applied the DBS technique to evaluate drug concentrations in newborns, infants and children [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%